Effectiveness of Regulations and Institutions for Eradicating Corruption in Southeast Asia: A Comparative Study of Indonesia and Vietnam - Hidayat, Sarip; Suwari Akhmaddhian; Erga Yuhandra; Budiman, Haris; Lam Thanh Danh (Universitas Kuningan, 2025)
Corruption is a major problem in Southeast Asia because it slows down economic growth, reduces public trust, and can destabilize governments. Therefore, this study aimed to identify and analyze how corruption is addressed in Indonesia and Vietnam. A socio-legal method was used by combining normative analysis of anti-corruption rules. Data were obtained from statutory regulations, reports from anti-corruption institutions, journal articles, and international sources such as Corruption Perceptions Index. The results showed that in Indonesia, the fight against corruption was mainly led by Corruption Eradication Law and Law on Corruption Eradication Commission. Following the discussion, enforcement was conducted by Corruption Eradication Commission (KPK). In Vietnam, anti-corruption efforts were managed under Law on Anti-Corruption and implemented through institutions such as Government Inspectorate and Central Steering Committee for Anti-Corruption Work. Indonesia had comprehensive regulations and an independent institution that played a significant role in investigating, prosecuting, and adjudicating corruption cases. However, changes made to the law in 2019 were observed by many as weakening the independence and effectiveness of the institution. Vietnam relied on a centralized method led by Communist Party through